(untitled) (Bangladesh Journal of Pharmacology, 2019)
The aim of the present study was to evaluate the effectiveness of e-learning (virtual class) in achieving procedural knowledge necessary to conduct practical class in the laboratory. In this study, teaching modules were prepared on eight selected topic related to pharmacology laboratory works. Virtual classes were conducted among the postgraduate MD students (n=26) of this Department. To know the existing procedural knowledge pre-test was taken before the classes and to evaluate the effectiveness of virtual class, a post-test was carried out seven days later. To get the feedback from students, two additional questionnaire surveys were done. The performance of each student improved in the post-test in comparison to the pre-test. Most of the students mentioned that virtual class was easier in comparison to face to face class. But they preferred combination classes to learn procedural knowledge.